REAL ESTATE DEVELOPMENT: LEGAL NATURE, OPERATIONAL DYNAMICS, AND PERSPECTIVES IN CONTEMPORARY BRAZILIAN LAW - S. Camacho, Gustavo (Revista Gênero e Interdisciplinaridade, 2026)
Real estate development constitutes a complex legal transaction that combines elements of various traditional civil law institutions, generating specific rights and obligations for the parties involved. This article analyzes the legal nature of real estate development, its operational dynamics in five distinct phases, the rights and obligations of the parties, the mechanisms of legal protection, and contemporary trends in the Brazilian market. Based on doctrinal analysis by renowned authors, consolidated jurisprudence of the Superior Court of Justice, and statistical data from 2024-2025, the work demonstrates that real estate development has evolved from a simple purchase and sale contract into a sophisticated legal institution, endowed with specific consumer protections and asset guarantee mechanisms. The article concludes that, despite legislative advances, especially with Law No. 14,382/2022, controversial issues remain that demand legislative and jurisprudential reform, particularly regarding the nature of the purchaser’s right over the autonomous unit and the limits of the developer’s liability after the delivery of the work.